Énonciation et analyse du discours - Dominique Maingueneau (Corela)
The relation between enunciative pragmatics and discourse analysis have never been simple. The problem has been compounded by globalisation of research, because outside French-speaking countries enunciation has come to be considered as one of the main features of French discourse analysis. In this article I will examine the ambivalent rapport that French discourse analysis has had with enunciative pragmatics since its very beginning. The way one takes into account enunciative phenomena is tightly connected with the conception one has of discourse and discourse analysis. It quickly becomes apparent that there is no consensus about the role that enunciation plays.